التحكيم في منازعات العقود النفطية في القانون الليبي : دراسة مقارنة بالشريعة الإسلامية - محمد، عزالدين ابو بكر علي
The petroleum relationships in Libyan state came as a result of conflict between Third World countries and Western companies to control over the petroleum wealth. Therefore, those companies have set some conditions for stabilization of its contractual relations, and in order to prevent the state from nationalization of their properties, as well as settlement their disputes through arbitration, and internationalization of its contracts. However, the Libyan state and its institutions insisted to hold on to their immunities and legal concessions to avoid arbitration agreements and apply international laws to its oil contracts. This conflict led to increase hostility from Libyan state towards international commercial arbitration. Thus, this thesis examines the role of arbitration in petroleum dispute resolution in the Libyan law through analysis and criticism of the judgments which were issued in the Libyan oil disputes with Western companies which are regarded controversial in the legal arena. Moreover, an extrapolation the rules of Libyan arbitration law, relevant international conventions and compare them with Islamic law. This may act as a catalyst to identify and resolve the problems associated with arbitration of petroleum disputes. The thesis concluded that arbitration is the most appropriate mechanism to resolve petroleum disputes. However, it requires concerted efforts to improve its centres, through holding of conferences and scientific debates and intellectual dialogues to address the problems associated with arbitration. On the other hand, the Libyan state should honour their commitments contained in arbitration agreements, while retaining the right to apply its national laws on oil contracts. Furthermore, it is also shall to legislate new laws to regulate arbitration and oil relationships with the inclusion of principles of Islamic law.